Antimicrobial Activity of Silver Nanoparticles Incorporated in a Cryogel Matrix - Illsley, Matthew; Bower, Cressida; Akhmetova, Alma; Kulsharova, Gulsim; Saliev, Timur; Nurgozhin, Talgat; Mikhalovsky, S. V. (27, h European Conference on Biomaterials, Krakow, Poland, 2015)
Hospital acquired infections are a major financial and societal burden with high mortality, morbidity and cost. Such infections are caused by a number of pathogenic and opportunistic bacteria, many of which are resistant to front line antibiotics. To combat their emergence and spread, new approaches have been developed such as adding biocides to wound dressings and surgical implants, but have met with limited success. We proposed an innovative technology capable of improving the clinical outcomes associated with bacterial infection of skin, deep wounds and surgical implants. This approach will exploit the ability of silver nanoparticles (NPs)1 to produce antibacterial radicals and reactive compounds. To begin with, antimicrobial activity of NPs and cytotoxicity of materials were tested.
Keywords: polymerization; antimicrobial activity of silver